Odd landscape elements: slag heaps in the region of Salgótarján (North Hungary) - Angyal, Zsuzsanna; Szabó, Mária; Karátson, Dávid (JOURNAL OF LANDSCAPE ECOLOGY, 2004)
The industrial works of the town of Salgótarján, a centre of heavy industry during the socialist regime, have been polluting the surroundings for dozens of years. This includes air, soil, surface and subsurface water pollution as well. Apart from these, a special form of environmental pollution exists, namely the presence of slag heaps of an old power station, which can be difficulty harmonized with natural landscape. We have found the investigation of those cones very important. The study of the two slag heaps is very important from several point of view. Studying the morphology of the cones, we made a field survey and evaluated the available air photos, and concluded on the qualitative and quantitative characteristics of degradation. The qualitative aspect includes the reconstruction of the erosion occurred in the past thirty years. Namely, we have pointed out that, apart from rill erosion, the slides that propagate upward on the cone surfaces also play an important role. The latter, quantitative study, based on the present cone dimensions and the volume of rills of the cones, has resulted in the calculation of the eroded material and average erosion rate. In the past 30 years, ca. 10-15 % of the cone volume has been removed, implying serious environmental risk. Furthermore, the analytical composition of the slag was also determined. The method of X-ray fluorescence was used. This method enabled us to determine the chemical elements on a qualitative and quantitative ground. Because of the radioactive heavy elements, it is reasonable to investigate radioactivity as well. The recovery of vegetation by the secondary succession might play an important role in reducing the pollution. That process, however, is going on mostly on the elder slag heap surfaces only. The changes of plant cover was followed by using aerial photos. On the elder heap – taking into consideration of different exposure – the survey for the determining plant structure was made. On the basis of ecological and naturelness (conservation) values it can be stated that the surface of heaps are colonizes mostly by weed and disturbance tolerate species, characteristics for ruderal habitats forming specifying succession states. Subsequently, the perennial herbaceous as well as arboreal plants are also occurring. On the studied heaps only spontaneous plant colonisation and vegetation recovery is taking place. The plant cover is strongly mixed, it doesn’t form typical communities, so it is quite unique. On the basis of our results a plan for landscape rehabilitation can be made in the future.